2016
DOI: 10.1097/jcp.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-Release Buprenorphine (RBP-6000) Blocks the Effects of Opioid Challenge With Hydromorphone in Subjects With Opioid Use Disorder

Abstract: A major goal for the treatment of opioid use disorder is to reduce or eliminate the use of illicit opioids. Buprenorphine, a µ-opioid receptor partial agonist and kappa opioid receptor antagonist, is now being developed as a monthly, sustained-release formulation (RBP-6000). The objective of this study was to demonstrate that RBP-6000 blocks the subjective effects and reinforcing efficacy of the µ-opioid receptor agonist hydromorphone (intramuscularly administered) in subjects with moderate or severe opioid us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…A US study demonstrated that a 300 mg dose of RBP-6000 provided a potent blockade of the subjective effects and reinforcing efficacy of hydromorphone in subjects with moderate or severe OUD. 74 In addition, pharmacokinetic analysis of RBP-6000 showed that a subcutaneous dose of 300 mg every 28 days rapidly achieved effective drug exposure after the initial injection and maintained effective levels during chronic treatment. A simulated 2-week drug holiday demonstrated μ-opioid receptor occupancy consistently above 80% without loss of drug efficacy.…”
Section: New Medication Delivery Approaches For Treating Oudmentioning
confidence: 99%
“…A US study demonstrated that a 300 mg dose of RBP-6000 provided a potent blockade of the subjective effects and reinforcing efficacy of hydromorphone in subjects with moderate or severe OUD. 74 In addition, pharmacokinetic analysis of RBP-6000 showed that a subcutaneous dose of 300 mg every 28 days rapidly achieved effective drug exposure after the initial injection and maintained effective levels during chronic treatment. A simulated 2-week drug holiday demonstrated μ-opioid receptor occupancy consistently above 80% without loss of drug efficacy.…”
Section: New Medication Delivery Approaches For Treating Oudmentioning
confidence: 99%
“…The ability of BUP to block the effect of full opioid agonists on the lOR has been shown in pharmacological 'blockade' or 'challenge' studies where patients are first administered BUP at different doses and then challenged with drugs such as heroin or hydromorphone [4]. There are some authors of scientific publications claiming that an adequate opioid blockade requires an 'optimal exposure' with BUP plasma concentrations of 2-3 ng/ mL and that this is achieved with a daily sublingual (SL) dose of BUP or buprenorphine/naloxone (BUP-NLX) of 16 mg and higher [5][6][7]. However, others suggest that further research is needed to understand dose-response relationships in patients with this complex disorder [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A total of nine subcutaneous injections were simulated in 5000 subjects. The horizontal red dashed line indicates the 2-ng/mL minimum concentration required for opioid blockade, as established from modeling and simulation and confirmed by clinical data (Nasser et al [18]) SL buprenorphine in Study 2 (where genotypes were measured), the effect of genetic covariates on SL bioavailability was not assessed.…”
Section: Discussionmentioning
confidence: 87%